Differential regulation of sodium channels as a novel proarrhythmic mechanism in the human failing heart. Issue 13 (20th June 2018) - Dybkova, Nataliya; Ahmad, Shakil; Pabel, Steffen; Tirilomis, Petros; Hartmann, Nico; Fischer, Thomas H; Bengel, Philipp; Tirilomis, Theodoros; Ljubojevic, Senka; Renner, André; Gummert, Jan; Ellenberger, David; et al.
Abstract: Aims: In heart failure (HF), enhanced persistent Na + current (INaL ) exerts detrimental effects on cellular electrophysiology and can induce arrhythmias. However, the underlying regulatory mechanisms remain unclear. Our aim was to potentially investigate the regulation and electrophysiological contribution of neuronal sodium channel NaV 1.8 in failing human heart and eventually to reveal a novel anti-arrhythmic therapy. Methods and results: By western blot, we found that NaV 1.8 protein expression is significantly up-regulated, while of the predominant cardiac isoform NaV 1.5 is inversely reduced in human HF. Furthermore, to investigate the relation of NaV 1.8 regulation with the cellular proarrhythmic events, we performed comprehensive electrophysiology recordings and explore the effect of NaV 1.8 on INaL, action potential duration (APD), Ca 2+ spark frequency, and arrhythmia induction in human failing cardiomyocytes. NaV 1.8 inhibition with the specific blockers A-803467 and PF-01247324 decreased INaL, abbreviated APD and reduced cellular-spontaneous Ca 2+ -release and proarrhythmic events in human failing cardiomyocytes. Consistently, in mouse cardiomyocytes stressed with isoproterenol, pharmacologic inhibition and genetically knockout of NaV 1.8 ( SCN10A −/− ), were associated with reduced INaL and abbreviated APD. Conclusion: We provide first evidence of differential regulation of NaV 1.8 and NaV 1.5 in the failing human myocardium and their contribution to arrhythmogenesis due to generation of INaL . We propose inhibition of NaV 1.8 thus constitutes a promising novel approach for selective anti-arrhythmic therapy in HF.